2008
DOI: 10.1097/hjr.0b013e3282f00990
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular remodelling in patients with moderate systolic dysfunction after myocardial infarction: favourable effects of exercise training and predictive role of N-terminal pro-brain natriuretic peptide

Abstract: Six month ET induced a favourable LV remodelling and a marked fall in NT-proBNP that could predict LV remodelling in postinfarction patients with moderate LV dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
79
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 34 publications
3
79
0
3
Order By: Relevance
“…The present study also confirmed the favourable effects of exercise-based CR on LV remodeling and function showed in previous studies in patients with previous AMI or CHF and more severe compromise of LV systolic function [11][12][13][14][15], and in postinfarction patients with only mild to moderate LV dysfunction [16].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study also confirmed the favourable effects of exercise-based CR on LV remodeling and function showed in previous studies in patients with previous AMI or CHF and more severe compromise of LV systolic function [11][12][13][14][15], and in postinfarction patients with only mild to moderate LV dysfunction [16].…”
Section: Discussionsupporting
confidence: 93%
“…Atrial fibrillation complicating AMI has adverse prognostic implications [10] and it is associated to a larger LA size [3]. It has been widely shown that exercise-based Cardiac Rehabilitation (CR) after AMI has beneficial effects on LV remodeling [11][12][13] and may even reverse this process in some patients with chronic LV dysfunction [14][15][16]. Exercise-based CR is also associated with reduced mortality in postinfarction patients [17].…”
Section: Introductionmentioning
confidence: 99%
“…Mounting evidence suggests that exercise training alone or as core component of cardiac rehabilitation (CR) programs has several beneficial effects reducing mortality [1], preventing cardiac remodeling [2,3], and improving cardiovascular functional capacity and myocardial perfusion [4][5][6][7]. The improvement of endothelial function [8], the anti-inflammatory properties [9,10], the improvement of neurohormonal and autonomic balance [11][12][13][14][15], and the reduction of oxidative stress [16] might be some of the putative mechanisms by which exercise training exerts its beneficial effects.…”
Section: Introductionmentioning
confidence: 99%
“…did not observed changes of BNP and proBNP plasma levels, after aerobic training of moderate intensity. Giallauria et al [21,28], showed a decrease of NT-proBNP circulating levels after three months of moderateintensity aerobic training, in patients with ventricular dysfunction after MI. Our data show that moderate-intensity aerobic training does not interfere with the natural course of NT-proBNP plasma level decrease, which usually occurs in the context of MI, associated to VR, as reported by Nagaya et al [29].…”
Section: Discussionmentioning
confidence: 99%